2016
DOI: 10.2141/jpsa.0150132
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Prolactin Receptor on the Surface of Quail Spermatozoa

Abstract: Prolactin receptor (PRLR) is expressed in a wide variety of tissues and mediates diverse biological actions of prolactin (PRL). In mammals, PRL signaling is thought to be involved not only in the process of spermatogenesis and steroidogenesis in the testis, but also in the survival of ejaculated sperm. In avian species, although the expression of PRLR with several variants in the testis was reported, the role of PRL in testicular function is still unclear. The aim of this study was to examine the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Studies have shown an increase in serum prolactin levels was reversed by nicotine cessation (18). In addition, it was observed that there was no difference in hormone concentrations between ex-smokers and non-smokers suggesting that quitting smoking helps to reduce the levels of this hormone (19).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown an increase in serum prolactin levels was reversed by nicotine cessation (18). In addition, it was observed that there was no difference in hormone concentrations between ex-smokers and non-smokers suggesting that quitting smoking helps to reduce the levels of this hormone (19).…”
Section: Discussionmentioning
confidence: 99%